Therapeutic Resevoirs: Implantable Therapeutic Reservoir Systems for Diverse Clinical Applications in Large Animal Models (Adv. Healthcare Mater. 11/2020). Issue 11 (10th June 2020) - Duffy, Garry P.; Robinson, Scott T.; O'Connor, Raymond; Wylie, Robert; Mauerhofer, Ciaran; Bellavia, Gabriella; Straino, Stefania; Cianfarani, Francesca; Mendez, Keegan; Beatty, Rachel; Levey, Ruth; O'Sullivan, Janice; et al.
Abstract : In article number 2000305 by Ellen T. Roche, Eimear B. Dolan, and co‐workers, a new regenerative reservoir platform (Regenervoir) is described for use in large animal models that are easily translated to human studies, with relevance to cardiac, abdominal, and soft tissue pathologies. Regenervoir incorporates multiple novel design features essential for clinical translation, with a focus on scalability, mechanism of delivery, fixation, and filling/refilling with a therapeutic cargo.